Peran Kepala Sekolah Dalam Mengatasi Stres Kerja Guru Di Masa Pandemi Pada SMPIT Ashabul Kahfi Tabalong - Sri Hartini Juni Astuti (STIT Syekh Muhammad Nafis Tabalong, 2022)
This study aims to describe the role of the principal in dealing with teacher work stress during the pandemic at SMPIT Ashabul Kahfi Tabalong. The subjects of this study were the principal, teachers, education staff of SMPIT Ashabul Kahfi Tabalong. Data were collected through interviews, observations and documentaries. The data processing technique uses data reduction, data display, and data verification and data analysis using qualitative descriptive. The results of this study indicate that the role of the principal in dealing with teacher work stress during the pandemic at SMPIT Ashabul Kahfi Tabalong, namely: 1) The role of the principal as an educator is to improve the quality of learning and provide guidance to teachers to implement a good teaching culture. In addition, it also instills, advances and improves four kinds of values, namely mental development, moral development, physical development, and artistic development. 2) The role of the principal as a manager is to empower teachers through collaboration, provide opportunities for teachers to improve their profession and also involve teachers in various activities that can support school programs. 3) The role of the principal as an administrator is to try to divide tasks as clearly as possible to teachers and school employees as well as assist in carrying out their duties as well as provide solutions if there are obstacles in the process. 4) The role of the principal as a supervisor is very serious in carrying out supervision to improve the quality of education, especially during this pandemic. 5) The role of the principal as a leader is to influence, mobilize, and empower existing resources in an effective and participatory manner in achieving school goals. The principal tries to be a good role model for his subordinates. 6) The role of the principal as a motivator is to always provide motivation and direction in the form of: religious activities, mental and counseling approaches, achievements, awards and coordination.